GENERAL AND BEHAVIORAL TOXICOLOGICAL EFFECTS OF SUBCHRONIC INORGANIC ARSENIC AND FLUORIDE TREATMENT IN ADULT WISTAR RATS - Sarkozi, K.; Mate, Z.; Vezer, T. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
Oral exposure of humans to excess amounts of arsenic and/or fluorine may cause nervous system disturbances. In the present study, such exposure was modelled in rats, with an examination of general and behavioural endpoints. Seven weeks old adult male SPF Crl: WI BR Wistar rats (160±20 g, 4 groups of 12 rats each) were treated with sodium (meta)arsenite (10 mg/kg b.w.; As), sodium-fluoride (5 mg/kg b.w.; F) and their combinations (As+F) per os by gavage, 5 days in a week, once a day for 6 weeks. An untreated control group was also used (Control). General toxicological parameters (body weight gain, food and water consumption) were measured daily. Behavioral investigations (rota-rod and open field) were done in the 4th and 6th weeks of treatment. Weekly body weight gain was significantly reduced in the As (vs. F) and As+F (vs. Control and F) groups from the first week onwards. This difference was seen during the whole treatment period and was more prominent from the second week on (As and As+F vs. Control and F). As, but not F, affected the relative weight of the liver, spleen and kidneys. Food and water consumption in the As and As+F groups was significantly reduced vs. Control and F, while a non-significant increase in water consumption was seen in Group F. In the open field test, As and As+F caused a significant decrease in rearing and ambulation and increased immobility and local activity, vs. Control and F. In the rota rod performance, no noteworthy change was observed. In the treatment scheme applied, significant effects on both general and behavioural endpoints by arsenic, but not by fluorine, were detected, which underlines the risk from environmental exposure.